2020
DOI: 10.1063/1.5128446
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics calculation of thermal conductivity and shear viscosity in two-component fully ionized strongly coupled plasma

Abstract: We present the results of calculations of thermal conductivity and shear-viscosity coefficients of ultracold single charged two-component classical Coulomb plasma by the method of molecular dynamics (MMD). The calculations are carried out in a wide range of Coulomb coupling parameters. The comparison with analytical expressions and calculations of MMD for the model of one-component plasma on a uniform background is presented for conditions where experimental measurements are lacking. The results obtained for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…A model is considered for a system of charged particles consisting of protons and electrons with a concentration n e = zn i (z is ion charge), interacting according to the Coulomb law and without any restrictions at large or small distances [17][18][19][20]. The calculation of the classical equations of motion is carried out in a cubic cell in a micro-canonical ensemble by means of periodic boundary conditions and the method of the nearest image.…”
Section: Physical Model and Calculation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A model is considered for a system of charged particles consisting of protons and electrons with a concentration n e = zn i (z is ion charge), interacting according to the Coulomb law and without any restrictions at large or small distances [17][18][19][20]. The calculation of the classical equations of motion is carried out in a cubic cell in a micro-canonical ensemble by means of periodic boundary conditions and the method of the nearest image.…”
Section: Physical Model and Calculation Methodsmentioning
confidence: 99%
“…In this paper, we continue to study the thermal conductivity and viscosity coefficients of fully ionized strongly coupled plasma [20], where our results of calculating the thermal conductivity and viscosity for two-component singly ionized plasma were rather briefly discussed. The results of calculations made by means of the MMD, within the framework of the Green-Kubo formalism, for the thermal conductivity and viscosity coefficients of two-component fully ionized classical Coulomb plasma having ion charges from one to three, calculations performed by means of the MMD, will be presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have conducted molecular dynamics (MD) simulations, which can analyze the physical motions of atoms and molecules. MD simulations are widely used for many advanced applications [28][29][30][31][32][33] or for obtaining basic physical parameters, such as electrical conductivity [34], surface tension [35], viscosity [36], diffusion coefficient [37], and wettability [38]. They are also employed for ion extraction of electrospray thrusters because electrospray phenomena occur on an atomic scale [35,[39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have already shown that the PP model is feasible for contributing to real applications that require high accuracy of collisions, e.g. electron-ion temperature relaxation problems occurred in inertial confinement fusion (Zhao 2017(Zhao , 2018a; calculations of conductivity and diffusion coefficients in ultracold plasmas (Bobrov et al 2011;Bobrov, Vorob'ev & Zelener 2018;Bobrov et al 2019Bobrov et al , 2020 and some fundamental non-Maxwellian plasma relaxation problems (Zhao 2018c). In addition, the idea of PP in general has some other beneficial applications.…”
Section: Introductionmentioning
confidence: 99%